A dangerous man [compact disc, unabridged] - Crais, Robert (An Elvis Cole and Joe Pike novel, 2019)
When Joe Pike witnesses men abducting a woman, he chases them down, and two men are arrested. Then the woman disappears, and it's the beginning of big trouble for Joe and Elvis Cole.